Local Resistances of Gas–Liquid Two-Phase Flows in Vertical L-Shaped and Z-Shaped Pipes - Bing Wang; Shan-qun Chen; Bin Liao (International Journal of Chemical Engineering)
In this paper, a systematic numerical study of the local resistance coefficients of vertical L-shaped and Z-shaped pipes for gas‒liquid two-phase flows under vertical conditions was carried out using a realizable k-ε turbulence model combined with a mixture model in Fluent software. Specifically, the influence of the Reynolds number Rel, the gas-phase volume rate α, the radius–diameter ratio R/D, the height–diameter ratio H/D, and the two-phase flow direction on the local resistance coefficient ξ were discussed in detail. ξ of the vertical Z-shaped pipe decreases with increasing Rel, while ξ of the vertical L-shaped pipe does not change significantly. In a specific range, ξ of vertical L-shaped and Z-shaped pipes increases with increasing α and decreases with increasing R/D. In Z-shaped pipes, under the upward flow condition, ξ increases with increasing H/D, and under the downward flow and horizontal flow conditions, ξ first decreases and then increases with increasing H/D. Overall, upward and downward flow conditions have a larger ξ than the horizontal flow condition. When H/D is larger than 14, ξ tends to be stable under all three flow conditions. Finally, the relationship equations between ξ and Rel, α, R/D, and H/D were fitted, which agreed with the numerical results.